Câncer e agentes antineoplásicos ciclo-celular específicos e ciclo-celular não específicos que interagem com o DNA: uma introdução - Almeida,Vera Lúcia de (2005)
The chemotherapy agents against cancer may be classified as "cell cycle-specific" or "cell cycle-nonspecific". Nevertheless, several of them have their biological activity related to any kind of action on DNA such as: antimetabolic agents (DNA synthesis inhibition), inherently reactive agents (DNA alkylating electrophilic traps for macromolecular nucleophiles from DNA through inter-strand cross-linking - ISC - alkylation) and intercalating agents (drug-DNA interactions inherent to the binding made due to the agent penetration in to the minor groove of the double helix). The earliest and perhaps most extensively studied and most heavily employed clinical anticancer agents in use today are the DNA inter-strand cross-linking agents.